2015
DOI: 10.1097/mpa.0000000000000175
|View full text |Cite
|
Sign up to set email alerts
|

Potential New Pharmacological Agents Derived From Medicinal Plants for the Treatment of Pancreatic Cancer

Abstract: In the present article, we reviewed plants and phytochemical compounds demonstrating beneficial effects in pancreatic cancer to find new sources of pharmaceutical agents. For this purpose, Scopus, PubMed, Web of Science, and Google scholar were searched for plants or herbal components with beneficial effects in the treatment of pancreatic cancer. Data were collected up to January 2013. The search terms were "plant," "herb," "herbal therapy," or "phytotherapy" and "pancreatic cancer" or "pancreas." All of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 0 publications
1
14
0
1
Order By: Relevance
“…Some in vitro studies have demonstrated synergistic effects in relation to reduction of the levels of proinflammatory cytokines (45,46), as well as synergistic antioxidant activities (47). Other investigations have also demonstrated that resveratrol and curcumin have synergistic anti-cancer activity (22,(49)(50)(51)(52)(53)64), as well as cardioprotective activity (54). In fact, with respect to carcinogenesis, Malhotra et al (53) conducted an in vivo study to verify the effects of curcumin and resveratrol in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Some in vitro studies have demonstrated synergistic effects in relation to reduction of the levels of proinflammatory cytokines (45,46), as well as synergistic antioxidant activities (47). Other investigations have also demonstrated that resveratrol and curcumin have synergistic anti-cancer activity (22,(49)(50)(51)(52)(53)64), as well as cardioprotective activity (54). In fact, with respect to carcinogenesis, Malhotra et al (53) conducted an in vivo study to verify the effects of curcumin and resveratrol in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It has been commonly used as a food additive or dietary pigment and in traditional medicine [ 12 , 13 , 14 , 15 , 16 ]. Preclinical in vitro and in vivo studies have demonstrated that curcumin has several pharmacologic effects, including antioxidant, anti-inflammatory, and anticancer activities, in different types of cancer, including PC, by modulating multiple signaling pathways [ 15 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Taken together, these results suggest that curcumin can be considered a new therapeutic drug in PC treatment [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, not surprisingly, diet and other chemical factors are increasingly being recognized for their importance in PDAC development and progression, even treatment [ 78 , 79 , 80 ]. Azimi et al [ 81 ] originally identified 12 natural compounds with beneficial effects against PDAC cells through four or more mechanisms. Several of these have been evaluated and found indeed to be inversely associated with PDAC risk [ 82 ].…”
Section: Dietary Considerationsmentioning
confidence: 99%